SUPERIOR STRATEGY: IMPROVING THE QUALITY OF READING THE YELLOW BOOK - Ashiddiqi, Muhammad Naufal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores and analyzes the superior strategies implemented in the Tamhidiyah Program at Ma'had Aly Nurul Jadid to improve the quality of reading the Yellow Book among students. This research highlights learning innovations, including using the Nubdzatul Bayan book, memorization methods, and turret books as a source of knowledge and insight. Data was collected through observation, interviews, and documentation using qualitative methods. The research results revealed that the superior strategy implemented by Ma'had Aly succeeded in improving the quality of reading the Yellow Book among students. This article details the concrete steps taken by the Islamic boarding school in implementing this strategy, providing in-depth insight into educational innovation at Ma'had Aly and its relevance to the future development of Islamic education. Hopefully, this research can positively contribute to understanding and developing the yellow book learning method in the Islamic boarding school environment.